PENGARUH PERCEIVED QUALITY DAN VALUE FOR MONEY TERHADAP LOYALTY DALAM PENGGUNAAN APLIKASI CANVA PRO - Pagau, Dwi Wahyu; Dudi Anandya (FEB Universitas Sam Ratulangi Manado, 2024)
This study aims to examine the effect of perceived quality and value for money on loyalty with the help of other variables such as satisfaction and trust in using the Canva Pro application. In this study, 160 respondent’s data were collected by distributing questionnaires online using Google Form. The criteria for respondents sought from this study are at least 18 years old and have subscribed to Canva Pro for at least 3 months. This research uses the Structural Equation Modeling (SEM) approach and the Analysis of Moments Structures (AMOS) program used for data analysis. The results of this study indicate that perceived quality has a significant and positive effect on satisfaction, value for money has a significant and positive effect on satisfaction, satisfaction has a significant and positive effect on trust, satisfaction has an insignificant and positive effect on loyalty, trust has a significant and positive effect on loyalty, perceived quality has an insignificant and negative effect on trust.